Pelatihan Teknologi Ekstraksi Rimpang Jahe (Zingiber officinale) pada Masyarakat Kampung Jahe Kelurahan Karasak-Astanaanyar: Ginger (Zingiber officinale) Rhizome Extraction Technology Coaching for the people of Kampung Jahe, Karasak-Astanaanyar Sub District - Aryani, Ratih; Yuliawati, Kiki Mulkiya; Lukmayani, Yani; Lestari, Fetri; Sadiyah, Esti Rachmawati; Aprilia, Hilda (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The people of Ginger Village at Karasak Urban Village support the urban greening program by planting ginger plants in the yards and roadsides. Ginger is a traditional medicinal plant commodity that has the potential to be cultivated and developed into health products because of its various pharmacological effects. The PkM team has conducted Community Service Activities for active PKK cadres in Jahe village. This activity aims to educate residents of Ginger Village through PKK cadres about the importance of knowing reasonable ginger extraction procedures so that the benefits of ginger can be optimal as a nutritious ingredient with pharmacological effects. The service method is training in processing ginger using the infusion method. The results showed an increase in participants' knowledge of up to 67%, which indicates that PKK cadres could understand how to extract ginger correctly to maintain its quality and properties.